Can research help to deliver the promises of inclusive education? The case of students with disabilities in the education marketplace - Waitoller, Federico R.; Beasley, Letrice; West, TaMia; Randle, Stacy (Frontiers in Education, 2022)
In this paper, we engage with the question that that frames this special issue: Can research help to deliver the promises of inclusive education? We argue that the answer is not so much a sounding and unquestionable Yes! but more of a yes but… but it depends on what we consider and privilege as research evidence. Using the case of market-driven reforms and their impact on inclusive education for students with disabilities, we question the overemphasis on quantitative research as unbiased rationale for distributing economic and human resources, closing schools, and expanding private/public partnerships to deliver public education. We recommend that policy decision-making account for the history and geography of school districts and the intersectional forms of exclusion experienced by students and families, particularly those who experience interacting forms of oppression at the intersections of disability, race, and class.